Studi Pengendalian Banjir Kali Wrati Kabupaten Pasuruan - Rizal Arifuddin K.; Donny Harisuseno; Very Dermawan (Jurnal Teknik Pengairan, 2014)
Wrati River is a collector of Sangar River, Nyangkring River, Pagak River, and Bangiltak River, that located in Beji Sub Regency, Pasuruan Regency, East Java Province. Inundation in settlement and agricultural areas that caused by flood from Wrati River is a problem that occurs every rainy season. This study aims to determine the return period of flood and the alternative of flood control system. Result of the study shows that the amount of Wrati River’s flood is 17,294 m /s equal to return period 25-year flood discharge. The first alternative of flood control system by using Hydrologic Engineering Centers River Analysis System 4.1 (HEC-RAS 4.1) are river normalization and dyke construction that is combined with interconnection between Wrati River and Bangiltak River. Interconnection are connected by two side weirs in Stations 125 and Stations 165 with 5-m-wide and 9-m-wide, which discharge capacity are 14 m 3 /s and 30 m /s. The second alternative of flood control system is constructing two retarding basins. Capacity of the retarding basins are 1.603.425,65 m 3 3 and 3.201.424,83 m 3 .